The role of context in creating meaning - Ilona Lekhner; Huszti Ilona; Лехнер Ілона; Густі Ілона; Lechner Ilona (ТОВ Друкарня “Рутаˮ, 2021)
Abstract. The article examines the concepts of meaning and context and the relationship between them from the perspective of different linguistic disciplines. It deals in detail with the meaning creating process and its contextual nature. In defining the concepts in focus, it bases on the main theoretical theses of objectivists (linguistic structuralism) and experientialists (linguistic cognitivism). The main purpose of the article is to seek and explain consensus and differences between different approaches and theories.
Keywords: context; meaning; meaning creation; cognitive metaphor theory